2018
DOI: 10.4103/sajc.sajc_118_17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16INK4a and human papillomavirus 16 with associated risk factors in cervical premalignant and malignant lesions

Abstract: Introduction:Human papilloma virus (HPV) which is causative factor for cervical cancer may interact with p16 leading to malignant transformation of cervical epithelial cells. The present study was conducted to assess the immunoexpression of p16 INK4a in premalignant and malignant lesions of cervix and to correlate it with HPV 16 expression. It was also intended to study the various risk factors which may be associated with cervical cancer in this north Himalayan region of India.Material and Methods:The study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 13 publications
4
10
0
Order By: Relevance
“…The present study also showed that HPV 16 is uniformly present in cervical premalignant and malignant lesions and there is no difference in its expression with severity of the lesion. This is in concordance with previous study by Zouheiret al who have also observed that there is no significant difference in HPV detection rate between HSIL (high grade squamous intraepithelial lesion) and LSIL (low grade squamous intraepithelial lesion) or between HSIL and cervical cancer [11]. In the present study, it was found that maximum number of cases (90%) were positive for Ki-67, amongst which 56% showed grade 3 positivity while all controls (100%) were negative for Ki-67 expression.…”
Section: Discussionsupporting
confidence: 93%
“…The present study also showed that HPV 16 is uniformly present in cervical premalignant and malignant lesions and there is no difference in its expression with severity of the lesion. This is in concordance with previous study by Zouheiret al who have also observed that there is no significant difference in HPV detection rate between HSIL (high grade squamous intraepithelial lesion) and LSIL (low grade squamous intraepithelial lesion) or between HSIL and cervical cancer [11]. In the present study, it was found that maximum number of cases (90%) were positive for Ki-67, amongst which 56% showed grade 3 positivity while all controls (100%) were negative for Ki-67 expression.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, we found that p16 expression-and especially the cytoplasmic/nuclear p16 ratio-significantly distinguished HSIL from SCCC. Our findings are therefore evidence of the usefulness of p16 as a diagnostic biomarker between HSIL and SCCC, as previously proposed [18,19]. In fact, it has facilitated inter-observer agreement and then has improved the accuracy of traditional diagnostic methods based on histological observation in lower grade lesions [4][5][6]21,30].…”
Section: Discussionsupporting
confidence: 82%
“…Although p16 overexpression is a potential biomarker for CC clinical management [5,17,18], there is a lack of consensus [5,19] and standard guidelines [2] concerning its routine use. Similarly, the biological significance of the paradoxical activation of this tumor-suppressor protein in CC is not yet well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations